Pandemic Policing and Community Engagement: Preparedness, Legitimacy and Public Support During the COVID-19 Crisis in Nigeria - Aborisade, Richard A. (Criminal justice review, 2024)
This study brings to the fore, insights into three key factors that had been widely noted to play significant roles in driving effective pandemic policing. These are the preparedness of the police as first responders to a public health crisis, the level of public trust in the police as a legitimate power holder, and community engagement as a tool to drive public support and participation in fighting COVID-19. Using the Nigeria police as a case study, with the damning reports of abuse of power and other misconduct, this study examined how the police responded to COVID-19 mandates and community participation. Interviews with 40 police officers who enforced the COVID-19 lockdown, 16 senior police officers, and 18 community leaders within Lagos and Ogun states were conducted, and a thematic analysis of the narratives was carried out. Findings indicated that community engagement was not effectively deployed by the Nigerian police in the course of pandemic policing. This was due to a lack of police preparedness, over-reliance on the use of force for public control, public distrust in the police, and a lack of prior practice of community engagement by the police. Public distrust in the police was found to be central to peoples’ disobedience to COVID-19 rules which worsened police-community relations, culminating in protests against the police and its formations. These findings have important policy and practical implications if police legitimacy and post-COVID police-community relations are to improve.